A 2-watt, 0.15-µm GaAs pHEMT stacked amplifier at 22 GHz - Fersch, Thomas; Weigel, Robert; Quaglia, Roberto; Pirola, Marco; Ghione, Giovanni; Camarchia, Vittorio (MIKON, 2014)
elib2cris::1512001600,fersch2014

A CDMA Modulation Technique for Automotive Time-of-Flight LiDAR Systems - Fersch, Thomas; Weigel, Robert; Kölpin, Alexander (IEEE Sensors Journal, 2017)
We present the application of optical code division multiple access (OCDMA) modulation based on optical orthogonal codes for automotive time-of-flight light detection and ranging (LiDAR) system sensors using avalanche photodiode (APD) detectors. The modulation opens the possibility to discriminate single laser transmissions. This allows the realization of additional features like enhancing the systems’ interference robustness or accelerating their scanning rate. The requirements on automotive LiDAR OCDMA modulation differs from telecommunication’s demands in several ways: The sensor must guarantee absolute laser safety; front facing devices must be able to provide reliable long range results up to a distance of 150m and beyond; and the signal is transmitted through free space. After outlining the basic functionality of the sort of sensors in consideration, the properties of the optical orthogonal codes (OOC) modulation are compared with the state of the art theoretically. The influence of OOC parameters with respect to scanning LiDAR systems is examined. The modulation technique is then demonstrated experimentally with two examples: The detection and separation of coded and traditional signals is shown using a matched filter detection algorithm. In the same way, differently coded signals can be separated from each other. Impediments of the interference suppression quality are discussed. Finally, an overview of possible applications of the proposed technique in automotive LiDAR systems is given, which are enabled by the OCDMA modulation in the first place.
elib2cris::1512001600,fersch2017
Keywords: LiDAR; CDMA

A novel approach to non-invasive blood glucose measurement based on RF transmission - Hofmann, Maximilian; Fersch, Thomas; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (IEEE International Workshop on Medical Measurements and Applications, 2011)
A new approach to non-invasive blood parameter measuring is presented, which consists of two matched antennas for transmission based two port measurements. The current situation of patients suffering from diabetes mellitus and their need for novel blood sugar level measuring techniques is presented. Dielectric properties of body tissues are reviewed and their influence on transmission properties are estimated for plane wave propagation. A covered patch antenna and substrate integrated waveguide slot antenna has been designed, measured and compromised for glucose-concentration measurements. Further, several test locations are discussed with respect to an accurate measurement. The introduced antennas were optimized and fabricated with respect to the dielectric and mounting properties of human tissues.
elib2cris::1512001600,hofmann2011b

Challenges in Miniaturized Automotive Long-Range Lidar System Design - Fersch, Thomas; Weigel, Robert; Kölpin, Alexander (SPIE Defense + Commercial Sensing, 2017)

The Influence of Rain on Small Aperture LiDAR Sensors - Fersch, Thomas; Buhmann, Alexander; Kölpin, Alexander; Weigel, Robert (German Microwave Conference, 2016)
The influence of rain on pulsed LiDAR systems with a miniaturized aperture and small laser beam cross sections was investigated based on two situations deemed critical. First, discrete rain drops appearing very close to the laser aperture could lead to a complete deflection of the laser beam out of the original direction when drop and beam overlap. Our semi-probabilistic, semi-analytical model however indicates that the rate of deflected scan events is negligible. Second, the emitter surface could be, to a greater or lesser extent, covered with drops of various size, degrading the performance. We found an optimum ratio between drop diameter and laser beam diameter, favoring larger laser beams. Also this effect however is, in total, not critical.
elib2cris::1512001600,fersch2016
Keywords: LiDAR